Translations Between Logics: A Survey - Loffredo D'Ottaviano, Itala M.; Feitosa, Hercules de Araujo [UNESP]; Mras, G. M.; Weingartner, P.; Ritter, B. (Walter De Gruyter Gmbh, 2020)
In a series of previous papers we have studied interrelations between logics through the analysis of translations between them. In this paper, providing some brief historical background, we present a general survey of the main questions and problems we have analysed and the results we have obtained. As well as showing the interrelations between our concepts of conservative translation, contextual translation, abstract contextual translation, hypercontextual translation and the concept of isomorphism between logics, we discuss the interrelations among the distinct categories that are constituted by logics and the special types of translations between them.